Fodder shrub development in arid and semi-arid zones (International center for agriculture research in the dry areas, 2000)
The book contains the papers presented at the workshop organized to address the needs for rebuilding the vegetation cover that has been destroyed. The topics covered are the international experience with fodder shrubs, national experience with fodder shrubs, farmers and non-governmental organizations experience.